2019
DOI: 10.4103/jcd.jcd_216_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of angiogenesis using a novel platelet-rich product: An in vitro study

Abstract: Background: In vivo angiogenesis is normal and vital process in growth and development, wound healing, and formation of granulation tissue wherein new blood vessels form from preexisting vessels as part of revascularization. Platelet-rich products promote wound healing associated with angiogenesis. Biomaterials such as titanium were found to be angiogenic. Unlike in vivo situations, in vitro angiogenesis, study cells, within a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These observations were reproduced in embryonic kidney fibroblasts and in various cell lines such as HEK293, MG-63 osteosarcoma cells, human oral keratinocytes, SIRC, and 3T3 cells [18]. Mesenchymal cells, endothelial cells [23,42,55,63], epithelial cells [22], and macrophages [69] also responded to PRF with increasing proliferation. In contrast, PRF failed to induce proliferation of L929 fibroblasts [53] and human mesenchymal stem cells on collagen scaffolds [17].…”
Section: Selection Of Studiesmentioning
confidence: 60%
“…These observations were reproduced in embryonic kidney fibroblasts and in various cell lines such as HEK293, MG-63 osteosarcoma cells, human oral keratinocytes, SIRC, and 3T3 cells [18]. Mesenchymal cells, endothelial cells [23,42,55,63], epithelial cells [22], and macrophages [69] also responded to PRF with increasing proliferation. In contrast, PRF failed to induce proliferation of L929 fibroblasts [53] and human mesenchymal stem cells on collagen scaffolds [17].…”
Section: Selection Of Studiesmentioning
confidence: 60%
“…A previous dose-response study determined that the intracerebroventricular infusion of vascular endothelial growth factor (VEGF) increases vascular density with minimal associated brain edema at a concentration of 5 μg/ml [13]. It was found that titanium-prepared PRP (TPRP) has better angiogenic potential than its counterpart PRP [14]. These novel growth factor concentrates may be further studied for their effects on wound healing and their administration may be incorporated in CINPT.…”
Section: Positive Pressure Infusion With Growth Factor Concentrate Anmentioning
confidence: 99%
“…Also calcium hydroxide has become one of the most popular methods for pulp capping materials to form dentin bridge (2) . Mineral trioxide aggregate MTA has been an acceptable pulp capping material (3) . Moreover; many bio materials such as Platelets Rich Plasma (PRP), Platelets Rich Fibrin (PRF) have been used for direct pulp capping (4) .…”
Section: Introductionmentioning
confidence: 99%
“…So it has been proposed as possible medicament for pulp capping. Platelet-rich fibrin (PRF) is high platelet concentrate which improves soft and hard-tissue healing (3) . PRF has upper hand over the known PRP include ease of processing/application, minimal cost and no anticoagulant is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation